Physicochemical Parameters, Phytochemical Screening, and Antioxidant Activity of Capsicum annuum var. grossum Leaves From Indonesia - Mariani, Ria; Perdana, Farid; Mawaddah, Linda Rabbayani; Wibowo, Diki Prayugo (Journal of Midwifery and Nursing, 2024)
Dietary plants are believed to contain antioxidants that have positive effects on human health. Free radicals, other reactive oxygen and nitrogen spesies can be eliminated by antioxidants. The presence of flavonoids and phenol in paprika (Capsicum annuum var. grossum) fruit contributes to its antioxidant properties. The phytochemistry and antioxidant activity of paprika leaves—especially those cultivated in Indonesia—have not been extensively studied. The aim of this study to investigate psychochemical parameters, phytochemical screening and antioxidant activity of paprika leaves from Indonesia. Several physicochemical parameters and phytochemical screening test were done base on Indonesian Herbs Pharmacopoeia. Antioxidant activity test using DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Dry powder of paprika leaves have some physicochemical parameters which part of its characteristic. Dry powder and extract of paprika leaves contains flavonoid, saponin, phenol and steroid/triterpenoid. The findings of the antioxidant test indicated that the standard vitamin C exhibited an IC50 value of 6.22 µg/ml. In contrast, the extract, n-hexane fraction, ethyl acetate fraction, and water fraction demonstrated IC50 values of 6.41, 9.12, 8.96, and 10.58 µg/ml, respectively. There was potential for paprika leaves to be developed as a natural source of antioxidants.